Local voices, global impact: the changing trend of indigenous languages in transforming MTN Nigeria's advertising - Adeyeye, Babatunde; Salawu, Abiodun (Penerbit Universiti Kebangsaan Malaysia, 2025)
Integrating indigenous languages in MTN Nigeria's advertising signifies a powerful evolution in the company's approach. It underscores the value of local cultures while driving business growth. This study explores the changing trends in the use of indigenous languages in advertising practice, particularly in the context of globalisation. It focuses on MTN advertisements from 2019 to 2023 and the staff of advertising agencies in Lagos and Abuja. It is anchored on the theory of linguistic imperialism and the reception theory of communication. The study adopted the survey and content analysis research design and used the Snowball and purpose sampling methods. Findings show that while Pidgin is the most widely used indigenous language in advertising, the overall trend in MTN advertisements shows a decline in usage over the years, with occasional increases in specific years. Findings also highlight a growing recognition among consumers, as identified by respondents, of the importance of using Indigenous languages in advertising campaigns for culturally or regionally associated products despite the need for clear consensus on their efficiency. The study recommends advertising strategies that align with local linguistic identities to foster consumer engagement.